Pemanfaatan dan Penanaman Tanaman Obat Keluarga (TOGA) Menuju Keluarga Sehat Pada Ibu Pemberdayaan Kesejahteraan Keluarga (PKK) - Karamina, Hidayati; Supriyadi, Supriyadi; Firman Yasin, Dudella Desnani; Yusi Kamhar, Muhammad; Kusuma Astuti, Farida (Jurnal Inovasi Hasil Pengabdian Masyarakat (JIPEMAS), 2020)
The current development of the plants that have medicinal properties have progressed whereby drug discovery as well as a sophisticated new technology into alternative solutions in the pharmaceutical world progress. Utilization of the yard are generally not utilized properly has many benefits especially in terms of increasing the family income, for example as the granary of life and living pharmacy, so it needs to be developed intensively. Simple technology that can be implemented that should bring some broad benefits to society not only in the process of self-sufficiency, but also can be directed toward health independence through several development Family Medicinal Plants (TOGA). TOGA synonymous with herbal raw materials for herbal medicine which are domination with a bitter taste, has no aesthetic value and is rarely consumed by the public.Â  This causes difficulty in the development of the value of medicinal plants. to know and understand the background of the community in understanding the background of TOGA, how to grow TOGA plants, and their use to revitalize the TOGA program, especially in Sidorejo Village. This service activities subsequently conducted outreach activities about the benefits of medicinal plants, how crops TOGA is good and right as well as the provision of some medicinal plants will be planted in the yard of the village TOGA post. Of community service activities, it is concluded that the lack of knowledge of the public in knowing the types of plants TOGA and the efficacy of various plants TOGA limited and the lack of land use that are owned by citizens.